(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
As companies try to streamline operations and increase profits, human resource professionals are now looking at employees in a different light. In addition to finding the right candidate for the job, they are looking at how to cut costs per employee while still maintaining quality services for clients. The amount of money spent searching for, hiring, compensating and training an employee is examined and used to help determine profits and loss for a company. Analyze the value captured through employing contractors and part-time employees as a human resource strategy. As businesses look at new avenues to reduce overall costs, human resources management has evolved to include different types of employment, including more part-time employees and contractors. Particularly in light of the recent banking disaster (20082009), trends towards lower cost employment have grown increasingly common. HR professionals and departmental managers must be aware of the tradeoffs and opportunity costs of the models they chose to employ.